2005
DOI: 10.1248/cpb.53.422
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Plasma and Red Blood Cell Cholinesterase Activity of 53 Fruit Farm Workers Pre- and Post-Exposed Chlorpyrifos for One Fruit Crop

Abstract: Chlorpyrifos (O,O-diethyl 0-(3,5,6-trichloro-2-pyridyl) phosphorothioate) belongs to the organophosphate insecticide (OPs) family, and is widely used to kill aphids in fruit farms. The demand for this insecticide is increasing. To our knowledge, there is no biological monitoring data for fruitfarm worker exposure to chlorpyrifos insecticide is available in Thailand. Biological monitoring is an essential component of any comprehensive assessment of exposure. In fact, these farm workers were at high risk of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…This finding is in agreement with other studies carried out by Akgur et al (2003) and Joshaghani et al (2007). However, Thetkathuek et al (2005) demonstrated significant decrease in BuChE without alteration in AChE activity in chlorpyrifos applicators. Eaton et al (2008) stated that, plasma BuChE is substantially more sensitive to inhibition by chlorpyrifos than erythrocyte AChE.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with other studies carried out by Akgur et al (2003) and Joshaghani et al (2007). However, Thetkathuek et al (2005) demonstrated significant decrease in BuChE without alteration in AChE activity in chlorpyrifos applicators. Eaton et al (2008) stated that, plasma BuChE is substantially more sensitive to inhibition by chlorpyrifos than erythrocyte AChE.…”
Section: Discussionsupporting
confidence: 93%
“…Most other studies of pesticide exposure have used a study design with nonexposed controls (e.g., Cataño et al 2008; Ntow et al 2009; Rendón von Osten et al 2004) or a pre–post design (Gamlin et al 2007; Thetkathuek et al 2005) to identify cholinesterase depression. Such designs are not always practical with migrant workers in the eastern United States.…”
Section: Discussionmentioning
confidence: 99%
“…In economically developing countries like Thailand, organophosphates (OPs) and carbamates (CMs) are widely used as pesticides among fruit farmers [6]. Serious intoxication and other poor health repercussions resulting from the inappropriate use of insecticides are frequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Serious intoxication and other poor health repercussions resulting from the inappropriate use of insecticides are frequently reported. Due to the type of work performed, immigrant agricultural workers are at an especially high risk of being exposed to insecticides [7][8][9], a problem also reported in Kenya and Nicaragua [10,11] and in other areas of Thailand where insecticides are widely used in farming [6].…”
Section: Introductionmentioning
confidence: 99%